Solar PV: Investigating The Gap In Renewable Energy Policy Formulation And Implementation In Nigeria - Okoye, Chinedu (Advances in Social Sciences Research Journal, 2018)
This paper identifies a gap in, or between, the formulation and implementation of Renewable Energy (RE) policies in Nigeria. This gap, the paper submits, is the major factor behind the comparative lack of seeming progress in terms of societal appreciation/patronage, installation of Renewable Energy facilities and technology, acquisition of the required know-how for their maintenance and operation, poor RE energy/power generation, evacuation and distribution to the targeted end users. In making and backing up this submission, the paper evaluates key preliminary issues, the primary causative factors. Additionally, the paper runs an issue/comparative analysis. On the issue of societal apathy and lack of awareness, the paper carries out a survey directed at randomly picked citizens, in which their understanding, appreciation and willingness to patronise Renewable Energy is assessed. The paper, makes strategic recommendations that are practical and specific, and which if taken into consideration by concerned stakeholders especially the Government, at the policy formulation and implementation stages, will go a long way to bridging these gaps while ensuring a healthy energy mix for the benefit of the Country, and the attainment of the Vision 30:30:30.